The city of the excentric centres (Ciudades, 2017)
The article brings a particular reflection on centrality as a network of urban places. A decisive change in contemporary urbanization has been the creation of new places in cities –places configured in various settings such as “shopping malls”, revamped historic areas, sports arenas, multiplexes, museums, libraries– which try to “clone” qualities found elsewhere, or that create what is believed to assign quality to an urban space. The article acknowledges there are good possibilities for the issuing of human existential experiences in those places, contemplating them from the perspective of an increase in richer and more varied centralities stimulating social contacts. To demonstrate this it brings a selection of exemplary cities that count with off-center-centers. The paper brings advancements in the understanding of the concept of place; addresses the persistent concept of centrality and its new spatial correlations; and elaborates on centrality configured by excentric centers.
Keywords: place; centrality; excentric centers; urbanism; placemaking; placemarketing